2008
DOI: 10.1007/s10661-008-0673-z
|View full text |Cite
|
Sign up to set email alerts
|

A Stream–Wetland–Riparian (SWR) index for assessing condition of aquatic ecosystems in small watersheds along the Atlantic slope of the eastern U.S.

Abstract: As part of a regional study by the Atlantic Slope Consortium (ASC) to develop ecological and socioeconomic indicators of aquatic ecosystem condition, we developed and tested a protocol for rapidly assessing condition of the stream, wetland, and riparian components of freshwater aquatic ecosystems. Aspects of hydrology, vegetation, in-stream and wetland characteristics, and on-site stressors were measured in the field. The resulting metrics were used to develop an index of overall condition, termed the Stream-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…However image analysis is not a way to replace field work. We believe it provides some complementary sets of data (i) to combine with field information and (ii) to enlarge studied area (Rheinhardt et al, 2007;Brooks et al, 2009;Dufour et al, 2012). Indeed, although we provide illustrations that recent improvements in remote sensing science can provide 3D information for narrow strips of riparian vegetation with high temporal resolution, some variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However image analysis is not a way to replace field work. We believe it provides some complementary sets of data (i) to combine with field information and (ii) to enlarge studied area (Rheinhardt et al, 2007;Brooks et al, 2009;Dufour et al, 2012). Indeed, although we provide illustrations that recent improvements in remote sensing science can provide 3D information for narrow strips of riparian vegetation with high temporal resolution, some variables (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both scientists and managers need appropriate tools to monitor riparian vegetation: the latter for a quantitative evaluation of funded action efficiencies and the former for a detailed understanding of vegetation pattern and dynamic follow-up of restoration. Site or reach scale projects have numerous tools to assess riparian vegetation response to restoration practices (Munné et al, 2003;Coroi, 2006;Brooks et al, 2009). However, large scale projects need specific tools, capable of generating continuous and detailed data set along several river segments or at network scale (Tormos et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, images have good potential. In conclusion, image analysis can provide some complementary sets of data to combine with field information (Brooks et al, 2009) and objectives should be clearly identified before application.…”
Section: Limitations Of Image-based Approachesmentioning
confidence: 99%
“…During that project, we sought ways to blend similar research approaches being conducted between estuarine segments of coastal systems and the freshwater wetlands of small watersheds ). In addition, during development of a Stream-Wetland-Riparian Rapid Assessment Index (Brooks et al 2009), we needed a way to consistently describe components of aquatic ecosystems among ecoregions. Based on these experiences, we developed this regional classification system for the following reasons:…”
Section: Introductionmentioning
confidence: 99%